2021
DOI: 10.31236/osf.io/rvaw3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motives, barriers and preferences to physical activity in people with obesity: a systematic review

Abstract: Background. Although the benefits of physical activity (PA) are well known, physical inactivity is high in people with obesity. The objective of this systematic review was to i) appraise knowledge on PA motives, barriers, and preferences in individuals with obesity, and ii) quantify the most frequently reported PA motives, barriers and preferences in this population.Methods. Six databases (Pubmed, CINAHL, Psyarticle, SportDiscus, Web of science and Proquest) were searched until June 2020 by independent review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Conversely, a study conducted in China found that an increase of one standard deviation in air pollution, measured via the Air Quality Index (AQI, i.e., index combining carbon monoxide, nitrogen dioxide, ozone, sulphur dioxide, particulate matter measures), was related to a 7.3 hour increase in weekly self-reported sedentary time 15 . Among adults with obesity, studies report that weather conditions can be a barrier to physical activity 16,17 . Both higher (snow) precipitation and temperature are associated with lower physical activity levels among adults with severe obesity 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a study conducted in China found that an increase of one standard deviation in air pollution, measured via the Air Quality Index (AQI, i.e., index combining carbon monoxide, nitrogen dioxide, ozone, sulphur dioxide, particulate matter measures), was related to a 7.3 hour increase in weekly self-reported sedentary time 15 . Among adults with obesity, studies report that weather conditions can be a barrier to physical activity 16,17 . Both higher (snow) precipitation and temperature are associated with lower physical activity levels among adults with severe obesity 18,19 .…”
Section: Introductionmentioning
confidence: 99%